Needs Analysis and Expert Validation of an Inquiry-Based Science Module Integrated with Scientific Literacy - Syahriani Yulianci (Yayasan Insan Mulia Bima, 2025)
This study aimed to describe the results of a needs analysis and expert validation as an empirical basis for developing an inquiry-based Basic Science Concepts module integrated with scientific literacy to improve the science process skills (SPS) of prospective elementary school teachers. The study employed a Research and Development (R&D) approach, focusing on the needs analysis and initial product validation stages. Needs analysis data were collected from students and lecturers of the Basic Science Concepts course using a Likert-scale questionnaire, while the module was validated by three groups of experts, namely subject matter experts, media experts, and instructional experts. Data were analyzed descriptively using percentage scores based on predetermined feasibility criteria. The findings revealed that all five indicators of students' needs were categorized as very high (89.7%–94.1%), and all lecturers (100%) confirmed the urgency of developing the module as a teaching resource to support inquiry-based learning integrated with scientific literacy. Expert validation indicated that the module was highly valid in terms of content (93.73%), media (93.81%), and instructional aspects (94.58%), with an overall average validity score of 94.04%. In addition to demonstrating a high level of feasibility, the expert validation also provided constructive suggestions for improving the module's content, design, and presentation, all of which were addressed through minor revisions. These findings indicate that the module was developed based on empirically identified needs and has met the required standards of content, media, and instructional validity. Therefore, it is considered suitable for proceeding to a limited field trial to evaluate its practicality and effectiveness in enhancing the science process skills of prospective elementary school teachers.